Brazilian Unified Health System and democracy: nursing in the context of crisis - Janieiry Lima de Araújo; Rodrigo Jácob Moreira de Freitas; Maria Vilani Cavalcanti Guedes; Maria Célia de Freitas; Ana Ruth Macedo Monteiro; Lucilane Maria Sales da Silva
ABSTRACT Objective: to discuss, taking for reference the crisis in Brazil and its impact on public health policies, the insertion of Brazilian nursing in that context and its ways of practicing the profession, based on the study about the politicality of care. Method: the reflection is divided into two topics, the first is about public policies, the Brazilian Unified Health System and the deconstruction of the right to health with neoliberal offensive; and the second is about the nursing political action in the fight for the right to health and for democracy. Final considerations: we emphasize that nursing must assume its sociopolitical role to contribute to the construction of a better and fairer Brazil, saying no to neoliberal reforms, as well as fighting for rights already acquired and for the resumption of the democratic stability in the country.